Rotor Configuration for Cogging Torque Minimization of the Open-Slot Structured Axial Flux Permanent Magnet Synchronous Motors - Aycicek, E.; Bekiroglu, N.; Senol, I.; Oner, Y. (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2015)
In this study, the rotor structure of the double rotor single stator axial flux permanent magnet synchronous motor (AFPM) is optimized for minimizing the cogging torque without significantly changing the average torque of the motor. Three-dimensional (3-D) finite element analysis (PEA) is used for this optimization. Obtained results are compared with a base line reference axial flux synchronous motor.
Keywords: AFPM motor; FEA; structural analysis; surface permanent magnet motor; PM MACHINE; DESIGN; REDUCTION; Engineering; Telecommunications